2013
DOI: 10.1088/0004-637x/779/1/14
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a New Kind of Explosive X-Ray Transient Near M86

Abstract: We present the discovery of a new type of explosive X-ray flash in Chandra images of the old elliptical galaxy M 86. This unique event is characterised by the peak luminosity of 6 × 10 42 erg s −1 for the distance of M 86, the presence of precursor events, the timescale between the precursors and the main event (∼4,000 s), the absence of detectable hard X-ray and γ-ray emission, the total duration of the event and the detection of a faint associated optical signal. The transient is located close to M 86 in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
121
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(135 citation statements)
references
References 53 publications
14
121
0
Order By: Relevance
“…At this distance, the peak luminosity would be ∼ 2 × 10 34 erg s −1 which suggests an X-ray burst is unlikely (Galloway et al 2008). XRT 110103 exhibits similar properties to the transient XRT 000519 reported by Jonker et al (2013). Both evolve over a similar time-scale with the main burst taking place over a few hundred seconds and a slow powerlaw decay over the remainder of each observation.…”
Section: Xrt 110103supporting
confidence: 54%
See 4 more Smart Citations
“…At this distance, the peak luminosity would be ∼ 2 × 10 34 erg s −1 which suggests an X-ray burst is unlikely (Galloway et al 2008). XRT 110103 exhibits similar properties to the transient XRT 000519 reported by Jonker et al (2013). Both evolve over a similar time-scale with the main burst taking place over a few hundred seconds and a slow powerlaw decay over the remainder of each observation.…”
Section: Xrt 110103supporting
confidence: 54%
“…XRT 000519 shows some possible precursor events ∼ 4 and ∼ 8 ks prior to the main flare. Jonker et al (2013) found some spectral softening between the first and second bursts but did not display the spectral evolution of the source at greater time resolution. We have applied the same hardness ratio as for XRT 110103 and provide in Figure 3 an equivalent plot of the lightcurve and hardness ratio for comparison.…”
Section: Xrt 000519mentioning
confidence: 82%
See 3 more Smart Citations